PROSPEK PERKEMBANGAN LEMBAGA KEUANGAN MIKRO DI AMBARAWA: STUDI PENJAJAGAN KEBUTUHAN PENDAMPINGAN MASYARAKAT - Indroyono, Puthut; Krisdiono, Krisdiono; Subantoro, Renan; Priyono, Yosef Krido (Journal of Indonesian Economy and Business, 2002)
This research is a âsnapshotâ of the peopleâs economic problems especially of the socio-economic and cultural institutions in the villages in Kecamatan Ambarawa. The research has identified institutions and the so-called micro-finance institutions in the villages as initiated by both the people in the villages and by the village government. The government policies to mobilize the micro-finance institutions through top-down planning were carried out by various government institutions with limited success. It is now realized that it will be more effective and successful if it is implemented by the village people themselves in the form of self-reliance movement on micro finance.Keywords: micro-finance institution, ekonomi rakyat, participative development